Protecting Retail Investors in the Malaysian Capital Market - Tan, Petrina Tjin Yi (Journal of Malaysian and Comparative Law, 2017)
This paper examines the retail investor protection framework in Malaysia. It explains how although consumer protection and investor protection have similar characteristics, they have different developmental trajectories which have implications on the applicable regulatory approaches. This paper then provides a background of the capital market regulatory framework and retail investors in the Malaysian capital market context. It studies the classification of investors in the Malaysian framework, focusing on the distinctions between sophisticated and retail investors and argues for a more nuanced categorisation of investors to take into account modern market realities and international trends. While mandatory disclosure and investor education are critical parts of a functional securities regulation regime, it is argued that they are limited in their effectiveness in protecting retail investors. In view of the limitations of disclosure and investor education, this paper submits that regulatory paternalism is justified within certain parameters and considerations to ensure that retail investors are adequately protected.